Chronic non-puerperal uterine inversion: a rare case report - Gehlot, Hanslata; Choudhary, Praveen Kumar; Sharma, Seema (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Uterine inversion though a rare entity but whenever diagnosed it is mostly seen in post partam cases. Chronic uterine inversion in non-parturient female is even rarer. Here we report such a case of chronic uterine inversion in non-puerperal period. Treatment depends on the associated pathology and the stage of the inversion. In our case we performed abdominal hysterectomy.